PRÁTICAS RESTAURATIVAS: ALTERNATIVA DE MEDIAÇÃO DE CONFLITOS NA ESCOLA UMA OPÇÃO PELA HUMANIZAÇÃO DAS RELAÇÕES - Guimarães, Maria Isabel Maldonado (2013)
This research aimed to present in the form of case studies, the conflict through mediation of restorative practices in the school context. In this way it was intended to share a process occurred in a public school of a municipality in the State of São Paulo, which used restorative practices in conflict mediation with first year students. This is a survey that used case studies to build knowledge that can be socialized and that resulted in a change in the practice. The analysis was done by means of through reflective records, document analysis and observations. In the process of mediation, restorative practices were used, being the instrument the restorative circles aimed at conflict resolution and the prevention of violence through dialogue, reflection and an agreement between the parties. This research showed that the circles led to the reflection of children on their actions, the dialogue between all the segments involved, the strengthening of moral values, stimulating the use of mediation for the resolution of conflict situations so assertive and building a collaborative environment that served towards the prevention of violence. The principles of restorative justice have favoured the development of moral autonomy, cooperation in the school environment and the restoration of relations.